Problems of the Topical Field â€œArtâ€ in Modern School - Pavlovich Roshchin, Sergey; Maratovna Nizamutdinova, Svetlana; Pavlovna Shipovskaya, Lyudmila; Chinchorovich Bartsitz, Rauf (International Journal of Engineering and Technology, 2018)
The paper presents key factors of the â€œArtâ€ topical area within school education in modern Russian Federation. The â€œArtâ€ topical area is central to the entire process of molding a creative, harmoniously developed personality. Teaching musical, artistic, spiritual, and moral components is essential for high-quality education. The authors of the paper have reasonably substantiated the need for the active introduction of art to school curricula. The authors also manifested the importance of revealing studentsâ€™ creative potential and the development of their constructive skills. Of much importance is the fact that specific ways of improving the quality of school musical and artistic education emerge from the research results.Â Â